2017
DOI: 10.1159/000477534
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Human Inner Ear in the Cogan Syndrome with Cochlear Implantation

Abstract: The Cogan syndrome is a rare disorder characterized by nonsyphilitic interstitial keratitis and audiovestibular symptoms. Profound sensorineural hearing loss has been reported in approximately half of the patients with the Cogan syndrome resulting in candidacy for cochlear implantation in some patients. The current study is the first histopathologic report on the temporal bones of a patient with the Cogan syndrome who during life underwent bilateral cochlear implantation. Preoperative MRI revealed tissue with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…Bacciu noted that this ossification may not be identified on pre‐operative imaging, with 3 cases having clear imaging but findings of intraoperative osteogenesis 23 (all patients had Cogan's syndrome). Of the 14 studies (43 patients) that mentioned intra‐operative findings, 53.5% (23 patients) were found to have unilateral or bilateral fibrosis or osteogenesis of a section of the cochlea (14 Cogan's syndrome, 1 Vogt‐Koyanagi‐Harada syndrome, 1 neurosarcoidosis, 1 PAN, 6 not specified), 6,8,9,23,28,30‐35 10 of which required a drill out (7 Cogan's syndrome, 1 PAN, 2 unknown) 8,9,23,28,31 . In 6 patients, electrodes were still unable to be placed within the scala tympani (ST) and therefore the scala vestibuli (SV) was used (4 Cogan's syndrome, 1 Vogt‐Koyanagi‐Harada syndrome, 1 neurosarcoidosis) 6,23,30,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Bacciu noted that this ossification may not be identified on pre‐operative imaging, with 3 cases having clear imaging but findings of intraoperative osteogenesis 23 (all patients had Cogan's syndrome). Of the 14 studies (43 patients) that mentioned intra‐operative findings, 53.5% (23 patients) were found to have unilateral or bilateral fibrosis or osteogenesis of a section of the cochlea (14 Cogan's syndrome, 1 Vogt‐Koyanagi‐Harada syndrome, 1 neurosarcoidosis, 1 PAN, 6 not specified), 6,8,9,23,28,30‐35 10 of which required a drill out (7 Cogan's syndrome, 1 PAN, 2 unknown) 8,9,23,28,31 . In 6 patients, electrodes were still unable to be placed within the scala tympani (ST) and therefore the scala vestibuli (SV) was used (4 Cogan's syndrome, 1 Vogt‐Koyanagi‐Harada syndrome, 1 neurosarcoidosis) 6,23,30,32 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 studies were found to contain relevant data [11,12,[15][16][17][19][20][21][22][23][24][25][26], of which 10 studies were from MEEI [12,[15][16][17][21][22][23][24][25][26]. Duplicate subjects were identified and removed from the analysis, which left a total of 81 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…PRISMA 2009 flow diagram. A total of 13 studies were included in this quantitative synthesis [11,12,[15][16][17][19][20][21][22][23][24][25][26].…”
Section: Prisma Flow Diagrammentioning
confidence: 99%
“…Serologisch finden sich häufig Anti-körper gegen Antigene aus dem Innenohr, Hitzeschock-Protein 70 (HSP 70) oder auch das "Cogan-Peptid (CD148/Connexin 26 Homolog), sowie selten p-ANCA. Am ehesten handelt es sich hier jedoch um sogenannte "Bystander Effekte" [15,16,17].…”
Section: Pathogeneseunclassified